![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Answer:
\(6x^2-\left(2x+3\right)\left(3x-2\right)=7\)
\(\Rightarrow6x^2-\left(6x^2+9x-4x-6\right)=7\)
\(\Rightarrow6x^2-\left(6x^2+5x-6\right)=7\)
\(\Rightarrow6x^2-6x^2-5x+6=7\)
\(\Rightarrow-5x+6=7\)
\(\Rightarrow-5x=1\)
\(\Rightarrow x=\frac{-1}{5}\)
\(5x\left(12+7\right)-3x\left(80x-5\right)=-100\)
\(\Rightarrow5x.19-240x^2+15x=-100\)
\(\Rightarrow95x-240x^2+15x=-100\)
\(\Rightarrow-240x^2+110x+100=0\)
\(\Rightarrow-24x^2-11x-10=0\)
\(\Rightarrow24\left(x^2-\frac{11}{24}x+\frac{121}{2304}\right)-\frac{1081}{96}=0\)
\(\Rightarrow24\left(x-\frac{11}{48}\right)^2-\frac{1081}{96}=0\)
\(\Rightarrow24\left(x-\frac{11}{48}\right)^2=\frac{1081}{2304}\)
\(\Rightarrow\left(x-\frac{11}{48}\right)^2=\left(\frac{\pm\sqrt{1081}}{48}\right)^2\)
\(\Rightarrow\orbr{\begin{cases}x-\frac{11}{48}=\frac{\sqrt{1081}}{48}\\x-\frac{11}{48}=\frac{-\sqrt{1081}}{48}\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{\sqrt{1081}+11}{48}\\x=\frac{11-\sqrt{1081}}{48}\end{cases}}\)
\(\left(3x-5\right)\left(7-5x\right)-\left(5x-2\right)\left(2-3x\right)=4\)
\(\Rightarrow\left(21x-15x^2-35+25x\right)-\left(10x-15x^2-4+6x\right)-4=0\)
\(\Rightarrow36x-15x^2-35-16x+15x^2+4-4=0\)
\(\Rightarrow\left(-15x^2+15x^2\right)+\left(36x-16x\right)+\left(-35+4-4\right)=0\)
\(\Rightarrow30x-35=0\)
\(\Rightarrow x=\frac{7}{6}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(\Leftrightarrow6x^2-6x^2+4x-9x+6=7\)
=>-5x=1
hay x=-1/5
b: \(\Leftrightarrow5x\left(12x+7\right)-3x\left(80x-5\right)=-100\)
\(\Leftrightarrow60x^2+35x-240x^2+15x=-100\)
\(\Leftrightarrow-180x^2+50x+100=0\)
hay \(x\in\left\{\dfrac{5+\sqrt{745}}{36};\dfrac{5-\sqrt{745}}{36}\right\}\)
c: \(\Leftrightarrow21x-15x^2-35+25x-\left(10x-15x^2-4+6x\right)=4\)
\(\Leftrightarrow-15x^2+46x-35+15x^2-16x+4=4\)
=>30x-31=4
=>30x=35
hay x=7/6
![](https://rs.olm.vn/images/avt/0.png?1311)
1: \(A=\left(-x+5\right)\left(x-2\right)+\left(x-7\right)\left(x+7\right)\)
\(=-x^2+2x+5x-10+x^2-49=7x-59\)
\(B=\left(3x+1\right)^2-\left(3x-2\right)\left(3x+2\right)\)
\(=9x^2+6x+1-9x^2+4=6x+5\)
=>7x-59=6x+5
=>x=64
2: \(A=\left(5x-1\right)\left(x+1\right)-2\left(x-3\right)^2\)
\(=5x^2+5x-x-1-2x^2+12x-9\)
\(=3x^2+16x-10\)
\(B=\left(x+2\right)\left(3x-1\right)-\left(x+4\right)^2+x^2-x\)
\(=3x^2-x+6x-2-x^2-8x-16+x^2-x\)
\(=3x^2-4x-18\)
=>16x-10=-4x-18
=>20x=-8
hay x=-2/5
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x=\frac{7+4y}{3}\Rightarrow3x^2+4y^2=3.\left(\frac{7+4y}{3}\right)^2+4y^2=\frac{\left(7+4y\right)^2}{3}+4y^2\)
\(=\frac{49+56y+16y^2+12y^2}{3}=\frac{49+56y+28y^2}{3}\)
\(=\frac{28.\left(\frac{7}{4}+2y+y^2\right)}{3}=\frac{28.\left(y^2+2y+1+\frac{3}{4}\right)}{3}=\frac{28\left(y+1\right)^2+21}{3}\)
\(\ge\frac{21}{3}=7\)
Lời giải:
$|3x-2|=7$
$\Rightarrow 3x-2=7$ hoặc $3x-2=-7$
$\Rightarrow x=3$ hoặc $x=\frac{-5}{3}$
\(\left|3x-2\right|=7\)
\(\Rightarrow\left[{}\begin{matrix}3x-2=7\\3x-2=-7\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}3x=-5\\3x=9\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=-\dfrac{5}{3}\\x=3\end{matrix}\right.\)